2021
DOI: 10.1371/journal.pone.0256030
|View full text |Cite
|
Sign up to set email alerts
|

Aging characteristics of asphalt binders modified with waste tire and plastic pyrolytic chars

Abstract: Globally, the growing volume of waste tires and plastics has posed significant concerns about their sustainable and economical disposal. Pyrolysis provides a way for effective treatment and management of these wastes, enabling recovery of energy and produces solid pyrolytic char as a by-product. The use of pyrolytic chars in asphalt binder modification has recently gained significant interest among researchers. As asphalt binder aging influences the cracking, rutting, and moisture damage performance of asphalt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Bitumen modified with tire-waste-derived char exhibited higher aging resistance than virgin bitumen or bitumen modified with PP-waste-derived char, associated with their different spectroscopic and rheological indices. 29 The char-modified bitumen samples also showed good fatigue performance. Effects of additional modifiers, such as sulfur and synthetic aliphatic hydrocarbon wax (a byproduct of the Fischer-Tropsch synthesis process 65 ), were also explored.…”
Section: Use Of Plastic-or Tire-waste-derived Char As a Modifier For ...mentioning
confidence: 94%
See 2 more Smart Citations
“…Bitumen modified with tire-waste-derived char exhibited higher aging resistance than virgin bitumen or bitumen modified with PP-waste-derived char, associated with their different spectroscopic and rheological indices. 29 The char-modified bitumen samples also showed good fatigue performance. Effects of additional modifiers, such as sulfur and synthetic aliphatic hydrocarbon wax (a byproduct of the Fischer-Tropsch synthesis process 65 ), were also explored.…”
Section: Use Of Plastic-or Tire-waste-derived Char As a Modifier For ...mentioning
confidence: 94%
“…1-7 and 14 in Tables 2 and 3). 29,[37][38][39]45,57 They found that the two different chars enhance the high-temperature deformation resistance properties of bitumen. Bitumen modified with tire-waste-derived char exhibited higher aging resistance than virgin bitumen or bitumen modified with PP-waste-derived char, associated with their different spectroscopic and rheological indices.…”
Section: Use Of Plastic-or Tire-waste-derived Char As a Modifier For ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Aging indices are used to assess the aging performances of asphalt binder. The proportion of properties of asphalt binder after the aging occurred to the same properties before aging is known as aging index [ 39 ]. Indices of aging were determined from physical and rheological characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Biochar can also be added as an asphalt binder, increasing its high temperature performance and its resistance to aging [24]. Biochar from waste can also be added to epoxy resins, used in microelectronic, automotive and aircraft industries [27][28][29][30][31]. The adoption of biochar from more complex heterogenous sources such as municipal solid waste (MSW), contaminated wood and ASR could become a more viable option for the recycling industry.…”
Section: Introductionmentioning
confidence: 99%